Effect of Work Stress and Discipline on Employee Performance - Sri Padmantyo; Muhammad Aryasenna Abdurrahman (Urecol Journal. Part H: Social, Art, and Humanities, 2022)
This research aims to analyze the influence of work stress and work discipline on employee performance. The population and the sample of this research are employees who work in industrial companies in the Karanganyar area with a total of 190 employees as respondent. The type of data that used in this research is primary data. The data collection method is to distribute questionnaires in the form of print out questionnaires, then it will be processed by using SPSS Statistic 26 software. The result shows that work stress has a negative and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance.